2018
DOI: 10.1002/ccr3.1452
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax secondary to pulmonary alveolar microlithiasis

Abstract: Key Clinical MessagePulmonary alveolar microlithiasis (PAM) is a rare impairment of pulmonary phosphate clearance that leads to gradual precipitation of intra‐alveolar calcium phosphate microliths. There is often a striking difference between alarming clinical imaging and a relatively well patient. Pneumothorax in PAM often only respond to surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Pneumothorax is rare in PAM; one large review reported occurrence in 1.6% of patients [3]. There is some evidence that patients with PAM who develop pneumothorax may not respond to routine chest tube management and may require more aggressive pleural interventions such as talc pleurodesis or pleurectomy for resolution [31,32]. One patient with a 17 pack-year smoking history had three recurrences requiring pleurectomy and stapling of apical blebs [33].…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Pneumothorax is rare in PAM; one large review reported occurrence in 1.6% of patients [3]. There is some evidence that patients with PAM who develop pneumothorax may not respond to routine chest tube management and may require more aggressive pleural interventions such as talc pleurodesis or pleurectomy for resolution [31,32]. One patient with a 17 pack-year smoking history had three recurrences requiring pleurectomy and stapling of apical blebs [33].…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Devine et al [15] reported a 56-year-old Turkish man of PAM presented with mild dyspnea and a lifelong history of chronic lung disease. Despite pneumothorax, his patient was asymptomatic at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnoea, dry cough, fatigue, and chest pain are frequent complains in symptomatic patients. Pneumothorax, clubbing, haemoptysis, hypoxia, and cyanosis have been reported [2,3,9,[14][15][16]. Lung function is usually normal or has a restrictive pattern [2].…”
Section: Diagnosis Clinical Characteristics and Treatmentmentioning
confidence: 99%